Epithelial ovarian tumors: Clinicopathological correlation and immunohistochemical study - Pooja S Naik; Sanjay Deshmukh; Siddhi Gaurish Sinai Khandeparkar; Avinash Joshi; Shridhar Babanagare; Jyostna Potdar; Neelesh Sharad Risbud (Wolters Kluwer Medknow Publications, 2015)
Background: Ovarian cancer is the third leading site of cancer among women, trailing behind cervix and breast cancer. Aim: This study was undertaken to analyze the immunohistochemical (IHC) profile of estrogen receptors (ER), progesterone receptors (PR), Ki-67, and p53 in various ovarian epithelial tumors and attempt correlation with clinical and histopathological findings. Materials and Methods: The present study was conducted over a period of 4 years. A technique of manual tissue array was employed for cases subjected for IHC. The primary antibodies used were ER, PR, p53, and Ki-67. A correlation was attempted between histopathological and IHC findings. Results were subjected to statistical analysis. Software program "the primer of biostatistics 5.0" was used for calculation of interrelationships between the analyzed ER, PR, p53, and Ki-67 expression and histological factors by Pearson's Chi-square test. The results were considered to be significant when the P < 0.05. Results: There were 110 cases of surface epithelial ovarian tumors (SEOT) encountered over the period of 4 years. The expression of ER was more in malignant tumors (13/16, 81.25%) than borderline (9/12, 75%) and benign (20/82, 24.39%). As compared to ER, the expression of PR was more in benign (51/82, 62.19%) than borderline (8/12, 66.67%) and malignant tumors (9/16, 56.25%). The expression of PR was more in benign tumors than borderline and malignant tumors. However, this was not statistically significant (Chi-square = 0.335 with 2 degrees of freedom; P = 0.846). The expression of p53 was less in benign (5/82, 6.1%) than borderline (9/12, 75%) and malignant tumors (13/16, 81.25%). The expression of Ki-67 was more in malignant (4/82, 4.88%) than borderline (10/12, 83.33%) and benign tumors (15/16, 93.75%). In all the above cases, the difference was statistically significant (P < 0.05). There was statistically significant difference in the expression of ER, PR, p53, and Ki-67 in the patients with age <40 years and above 40 years (P = 0.912). A positive correlation was observed in p53 expression and tumor grade. Similar correlation was seen in Ki-67 and tumor grade. It was also noted that mean Ki-67 labeling index (Li) had also increased with tumor grade. In the case of serous tumors, ER was expressed in all high- and low-grade tumors. The expression of PR was more in low-grade tumors than high-grade ones. P53 expression was seen in all high-grade tumors and 33.34% of low-grade tumor. The Ki-67 Li was more in high-grade tumors than low-grade tumors. Expression of ER, p53, and Ki-67 was higher in tumor showing metastasis. The mean Ki-67 Li was also higher in metastasizing tumors. However, PR expression was less in metastasizing tumors than nonmetastasizing tumors. Conclusion: IHC marker report of ER, PR status, and Ki-67 if included in each pathology report will pave the way for better understanding of biological behavior and modify treatment strategies.